Requirement of Trichome Formation for the Growth-promoting Effects of Olivine for Enhanced Weathering in Arabidopsis thaliana - Minoru Ueda; Daisuke Todaka; Satoshi Takahashi; Junko Ishida; Maho Tanaka; Tokihiro Ikeda; Keiko Suzuki; Misako Miwa; Takeshi Uchiyama; Yasuhiro Ishimaru; Kazuhiro Sayama; Nobuyuki Uozumi; et al. (Journal of Plant Growth Regulation, 2026)
Enhanced rock weathering helps remove CO 2 from air and cools the Earth over geological time periods, while also promoting plant growth, but the molecular mechanism underlying enhanced plant growth is unclear. In this study, ionome and transcriptome analyses revealed the importance of trichome formation for the growth-promoting effects of olivine ground to enhance weathering. In Arabidopsis, the application of 10% (w/w) olivine improved plant growth (a 64.2% increase in leaf area) and caused a 24.7% increase in Mg accumulation determined by ICP-AES at 23 days after germination (DAG) under long-day (16 h light/8 h dark cycle) conditions. Elemental maps of olivine-treated plants at 10 DAG produced by micro-particle-induced x-ray emission showed that olivine significantly altered Mg, K, and S accumulation in trichomes on true leaves, suggesting that trichomes may be critical for olivine-induced growth. The growth of glabrous1 ( gl1-1 and gl1-4 ) mutants defective in trichome initiation was not promoted by olivine. A transcriptome analysis of shoots by RNA-seq from wild-type plants at 16 DAG indicated olivine suppressed biotic stress-responsive gene expression. Additionally, Zn homeostasis was disrupted by olivine in gl1 mutants, implying that decreased Zn availability may inhibit the positive effect of olivine on growth. Collectively, our data uncovered the importance of trichomes to the adaptation of plants to soils containing rock-powders for crop improvement and agricultural sustainability and suggest the possibility that applying olivine might modulate the growth–defense trade-off governed by ion homeostasis mediated through trichome development, leading to improved plant growth.

Distinct OPDA Biosynthesis Pathways in the Liverwort Marchantia polymorpha and the Moss Physcomitrium patens - Yuho Nishizato; Yuki Hata; Takuya Kaji; Mai Morikawa; Junko Kyozuka; Minoru Ueda (Journal of Plant Growth Regulation, 2026)

A Pyrazole Partially Induces Brassinosteroid-Related Gene Expression, Leading to Salt Stress Sensitivity - Minoru Ueda; Satoshi Takahashi; Junko Ishida; Ayumi Yamagami; Takeshi Nakano; Florian Pünner; Mai Akakabe; Yoshihiro Sohtome; Atsushi J. Nagano; Mikiko Sodeoka; Motoaki Seki (Journal of Plant Growth Regulation, 2025)

Characterization of an extracellular thermophilic chitinase from Paenibacillus thermoaerophilus strain TC22-2b isolated from compost - Junko Ueda; Norio Kurosawa (World Journal of Microbiology and Biotechnology, 2015)

A prospective cohort study of shift work and the risk of death from pancreatic cancer in Japanese men - Yingsong Lin; Junko Ueda; Kiyoko Yagyu; Michiko Kurosawa; Akiko Tamakoshi; Shogo Kikuchi (Cancer Causes & Control, 2013)

Hybrid lethality of cultured cells of an interspecific F1 hybrid of Nicotiana gossei Domin and N. tabacum L. - Masanobu Mino; Yuko Misaka; Junko Ueda; Ken’ichi Ogawa; Masayoshi Inoue (Plant Cell Reports, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)